Shuffled Multi-Track Detection for Shingled Magnetic Recording Channels With an Array of Read Heads - Han, Guojun (2016)
Shingled magnetic recording (SMR) with 2-D magnetic recording has recently emerged as a promising technology to sustain the growth of magnetic storage areal density. However, with the reduction of track pitch, the intertrack interference (ITI) becomes a major impairment. Furthermore, in SMR, the ITI is non-uniform among the top and lower tracks. A 2-D read channel which makes use of an array of read heads can effectively detect and compensate the severe ITI. In this paper, based on a read-array SMR channel model with non-uniform ITI, a shuffled multi-track detection (SMTD) detector, which shuffles and propagates the most reliable extrinsic information among the upper, lower, and middle detectors, is proposed to mitigate ITI more effectively. With the optimized non-binary low-density parity-check code, the performance of the proposed SMTD over the read-array SMR channel is evaluated.